PROBLEMATIKA PENERAPAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DI MADRASAH - Dede Rosyada; Wahdi Sayuti (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
AbstractKTSP (Kurikulum Tingkat Satuan Pendidikan) is a national policy which has been socialized into madrasahs. Development of KTSP is carried out by adopting a Content Tandard issued by Department of National Education (Departemen Pendidikan Nasional/Depdiknas), so that it needs a creaivity, integrity, and profesionalism of theachers and the managenent of madrasahs to construct the curriculum. The implementation of KTSP development at madrasahs is assumed will be experiencing some problems, many others, for example: (1) principals of madrasahs should motivate teachers to develop the classroom curriculum, while he himself is not experienced with dong so; (2) profesionalism of the teachers of madrasahs; (3) the facilities and infrastructures of madrasahs which are limited; and (4) teachers of madrasahs still have not been familiar with the learning models that encourage the activities of students in classrooms. Various parties, especially those are responsible for increasing educational quality of the madrasah, need to deal with thw abovementioned issues in a serious manner.